Assessment of python (Python bivittatus Kuhl.) habitats in Bardiya National Park, Nepal - Sharma, Bhuvan Keshar; Kandel, Ram Chandra (Ecoprint: An International Journal of Ecology, 2016)
Habitats used by the Python (Python bivittatus) were studied in lowland areas of Bardiya National Park, Nepal. The main objective of the study was to assess the specific habitats used by Python in the Park. In association with key informants’ survey to identify the potential habitats areas, field investigation was conducted and found out the specific sites. Among twenty habitat sites of Python, three were currently used and remaining other were found as potential habitats. In total, six specific habitats such as burrow or holes were mostly preferred by Python. ECOPRINT 22: 85-90, 2015